Preparing to Publish - Huffman, Sarah; Cotos, Elena; Becker, Kimberly (Open textbook library., 2023)
This book offers a wealth of instructional material on the topic of research article writing for publication and thesis or dissertation completion. The text provides graduate student writers with helpful information, strategies, and tips on navigating disciplinary writing in their fields and how to understand, dissect, and ultimately, construct their own research article. The text is organized according to a standard research article format, breaking down each section of the empirical research in a simple and straightforward manner to help graduate students build a quality, argument-driven manuscript as they write up their empirical study findings.